Left Behind? The impact of geographical mobility on children´s educational attainment in Finland and Germany - Patricia McMullin; Aleksi Karhula; Elina Kilpi-Jakonen; Jani Erola (Suomen akatemia, 2022)
It is often assumed that families migrate to improve their economic and social prospects, and that these additional resources can benefit the whole family. However, existing research suggests that many children who have experienced (internal) migration underperform compared to their non-migrating peers in terms of different socioeconomic outcomes. In this paper, we study the effects of geographical mobility on children’s educational attainment in Finland and Germany using Finnish register data and the National Educational Panel Study (NEPS) respectively. Our findings indicate that moving during childhood is associated with the risk of not attaining any secondary degree in both countries. In Finland, this is mostly explained by negative selection into moving, (i.e. those who move are more likely to be disadvantaged). For Germany however, an independent association between moving and educational attainment remains after taking into account various reasons why families move. Furthermore, for both Germany and Finland, any labour force status or earning gains parents make, after a move, do not seem to compensate for the negative influence of internal migration on children’s educational attainment. Overall, we conclude that that when children move something remains behind, therefore schools have an important role to play in integrating internal migrants – as well as international migrants – into the social networks of the schools they arrive in.